Development of X-Band Transceiver MMIC’s Using GaN Technology - O. Memioglu; O. Kazan; A. Karakuzulu; I. Turan; A. Gundel; F. Kocer; O. A. Civi (Advanced Electromagnetics, 2019)
This paper describes X-Band power amplifier (PA), low noise amplifier (LNA) and switches that can be used in transmit/receive modules which are developed with GaN technology. For Transmit chain two 25 W high power amplifiers that are tuned between 8-10 GHz and 10-12 GHz bands are designed. A low noise amplifier with 2 W survivability and less than 2dB noise figure is designed for receive chain Furthermore, an RF switch that is capable of withstanding 25 W RF power is developed for the selection of transmit or receive chains. Measurement results show that both power amplifiers produce 25 W of power. Low noise amplifier has more than 20 dB small signal gain with less than 2 dB noise figure. RF switch has 50 dB of isolation with less than 1 dB insertion loss.